The nexus between oil prices and stock prices of oil, technology and transportation companies under multiple regime shifts - Shaeri, Komeil; Katircioglu, Salih (Routledge Journals, Taylor & Francis Ltd, 2018)
This study investigates the interaction between crude oil prices and the stock prices of oil, technology and transportation companies listed on U.S. stock exchanges, using weekly data covering the period from 2 January 1990 to 3 February 2015. Considering the importance of regime shifts or structural breaks in econometric analysis, this study employs the Carrion-i-Silvestre, Kim, and Perron unit root tests and the Maki cointegration tests, allowing for multiple breaks. Cointegration results confirm the existence of long-run equilibrium relationships between these stock indices, crude oil prices, short-term interest rates and the S&P 500. These findings indicate that crude oil prices and the other explanatory variables are long-run determinants of the stock prices of oil, technology and transportation firms. Stock prices of oil companies are positively affected by crude oil prices to a greater degree than that of technology and transportation stocks. Time-varying causality results show that West Texas Intermediate crude oil (WTI) is relatively more likely to affect the stock prices of these companies rather than to be affected by them. Evidently, it is confirmed that financial crises have a substantial ability to intensify the causal linkages between WTI and the stock indices of these companies.
Keywords: Crude oil prices; stock prices; structural breaks; breakpoint regression; time-varying causality